Some management lessons in Sūrah Al-Baqarah based on the works of Khaled (n.d.) and Khan (2012) - Fontaine, Rodrigue Ancelot Harvey (IIUM Press, International Islamic University Malaysia, 2017)
This study explores some of the management lessons in Sūrah Al-Baqarah by referring to the explanations of Khaled (n.d.) and Khan (2012, 2016). Five management lessons were derived from Khaled (n.d.) and six management lessons were derived from Khan (2012, 2016). Khan (2012, 2016) was more detailed than Khaled (n.d.) and highlighted the problem of corrupt leadership. Leaders can became “spiritual people with a worldly mind-set” (Khan, 2012). The psychological and organizational processes that enable leaders to mislead their followers are then explored. Although one assumes that bad leaders are deliberately unethical, social psychology shows that good leaders can become bad unintentionally over time. Muslim business leaders can build one of three types of organizations. One with a positive organizational culture, one with a neutral organizational culture and one with a negative organizational culture. Similarly, Muslim employees have an ethical responsibility to seek employment in an organization whose corporate culture does not clash with Islamic values. As the Qur’ān provides timeless guidance, one can conclude that good and ethical leadership is an eternal challenge.